1989
DOI: 10.1007/bf00265302
|View full text |Cite
|
Sign up to set email alerts
|

Autopolyploidy in Dactylis glomerata L.: further evidence from studies of chloroplast DNA variation

Abstract: Chloroplast DNA variation has been used to examine some of the maternal lineages involved in the evolution of the intraspecific polyploid complex, Dactylis glomerata L. Diploid (2x) and tetraploid (4x) individuals were collected from natural populations of the subspecies glomerata (4x), marina (4x) and lusitanica (2x), as well as from sympatric 2x/4x populations of the Galician type. Digestion of their ctDNA with 11 restriction endonucleases revealed enough variation to characterise three ctDNA variants, desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 32 publications
4
36
0
Order By: Relevance
“…Thus, subspecies can act as a secondary gene pool (Stuczynski 1992). Relationships among the subspecies have been evaluated using morphological traits (Stebbins and Zohary 1959), chloroplast and ITS sequences (Lumaret et al 1989;Stewart and Ellison 2010), isozymes (reviewed in Lumaret 1988), and flavonoid compound diversity (Fiasson et al 1987), and each method has shown commonalities and differences. The SSR markers described herein have great resolution within the genus, which can aid in understanding the more recent genetic history of this species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, subspecies can act as a secondary gene pool (Stuczynski 1992). Relationships among the subspecies have been evaluated using morphological traits (Stebbins and Zohary 1959), chloroplast and ITS sequences (Lumaret et al 1989;Stewart and Ellison 2010), isozymes (reviewed in Lumaret 1988), and flavonoid compound diversity (Fiasson et al 1987), and each method has shown commonalities and differences. The SSR markers described herein have great resolution within the genus, which can aid in understanding the more recent genetic history of this species.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used a variety of tools: chloroplast and ITS sequences have been used to describe phylogenetic relationships (Lumaret et al 1989;Catalan et al 2004;Stewart and Ellison 2010), dominant markers (e.g., RAPD, ISSR, SRAP) used in discreet studies (Koelliker et al 1999;Tuna et al 2004;Peng et al 2008;Zeng et al 2008), and heterologous markers tested from other forage grass species Litrico et al 2009), However, the openplatform dominant markers generally have the inability to add samples to a study without re-analyzing all previous samples due to the large number of bands genotyped per primer. Heterologous marker transferability also decreases as species diverge (Thiel et al 2003;Zhang et al 2005;Litrico et al 2009), and are accompanied by higher likelihood of homoplasy and polymorphism due to mutations that exist among the species (Thiel et al 2003;Saha et al 2004;Zhang et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A strong genetic similarity between the Galician diploids and the tetraploids was revealed by means of isozyme profile and cpDNA restriction patterns (Lumaret 1984;Lumaret et al 1989). These results were also in good agreement with reports by Lumaret and Borrientos (1990), who assessed phylogenetic relationships between sympatric diploid and tetraploid plants of cocksfoot.…”
Section: Phylogenetic Relationships Of Diploid and Tetraploid Cocksfootmentioning
confidence: 99%
“…In areas where taxa of the same ploidy level of a single species occur sympatrically, habitat differentiation and\or reproductive isolation (say, differences in flowering time) may occur but generally, hybridization is possible, and might include subsequent genetic introgression between the taxa (Rieseberg & Wendel, 1993). These can become interconnected by a hybrid zone of genetically intermediate plants (Levin, 1983 ;Lumaret, Bowman & Dyer, 1989). The size of hybrid zone reflects the balance between random dispersal and the effect of selection.…”
Section: mentioning
confidence: 99%